Incentive contracts for politicians and the information efficiency of a democracy - Liessem, Verena (SSRN, 2003)
A campaign model in which candidates can make law announcements for reforms in the next term will be considered. Acquiring information about these laws incurs the candidates a certain cost. The conditions under which a candidate acquires information about a given law during the campaign will be presented and the factors determining the credibility of the law announcement will be explored. Furthermore, an incentive contract will be introduced which makes reelection dependent on the fulfillment of law announcements made during the campaign. The incentive contract increases the willingness of candidates to acquire information and hence increases the credibility of announcements. At the same time, the incentive contract may cause candidates to avoid introducing beneficial reforms. The dominating effect depends on the parameter constellation
Nach Informationen von SSRN wurde die ursprüngliche Fassung des Dokuments September 2003 erstellt